HOTS-Based Digital Worksheets as Interactive Assessment in Sciences Learning for Elementary School Teacher Education - Nurmawati, Fulusia; Setiaji, Soma; Ricardo, Angga (Universitas Negeri Padang, 2024)
This study was conducted because lecturers must be able to be more creative by carefully preparing Digital Worksheets for students, because they meet the criteria for basic competencies that must be mastered by students. The purpose of the article is to describe the implementation of HOTS-based Digital Worksheets as an interactive assessment in basic science learning for elementary school teacher education, identify supporting and inhibiting factors, and describe efforts to optimize supporting factors and efforts to overcome inhibiting factors. This study uses a descriptive qualitative research method, by describing a phenomenon as it is without manipulation. The research design chosen is a case study, meaning that the research is focused on one selected event or phenomenon in depth. The subjects of this study were 34 elementary school teacher education study program students who were in semester I. The sampling technique was purposive sampling. Data collection techniques are observation, interviews and document studies. Data validity techniques are technical triangulation and source triangulation. The results of this study is 71% of students felt that teaching materials with new innovations or in other forms. Form can increase students' interest in studying learning material.